Dental Applications of Nanotechnology (Springer International Publishing, 2018)
This book discusses current trends and potential applications of nanotechnology in dental materials. Dentistry is undergoing yet another change to benefit mankind via the discipline of nanodentistry. A variety of nanostructures such as nanorobots, nanospheres, nanofibers, nanorods, etc., have been studied for various uses in dentistry and medicine. Preventive dentistry has also utilized nanodentistry to develop nanomaterials for inclusion in a variety of oral health-care products. Methods to prevent and combat dental problems have been devised, discussed, and implemented since ancient times; however, there is a constant need for improved tools and techniques. This book is relevant academically for undergraduate and post-graduate dental students, dental practitioners, researchers, and faculties of dental universities, as this book explores the application of various nanobiomaterials in dentistry, discusses current research in dental nanomaterials and potential future areas of interest, and examines the use of nanotechnology in various fields of dentistry. Explores application of various nanobiomaterials to dentistry; Discusses current research in dental nanomaterials and potential future areas of interest; Examines the use of nanotechnology in several fields of dentistry. Dr. Ramesh S. Chaughule, Ex Scientist from Tata Institute of Fundamental Research, Mumbai, India, is an Adjunct Professor at Ramnarain Ruia College, Mumbai India, Research Advisor at Gogate Jogalekar College, Maharashtra, and a Fellow of Maharashtra Academy of Sciences. He is also the recipient of Indo-UK, Indo-USA, and Indo-Japan fellowships, and has more than 80 publications as papers and books in his field of research. He has also served on IAEA programs in Indonesia.